PENGARUH METODE PEMBELAJARAN EKSPRESI BEBAS TERHADAP KETERAMPILAN MENGGAMBAR SISWA KELAS IV SD NEGERI 102 PALEMBANG - Tiara Hadistsa Lukmara; Noviati; Robert Budi Laksana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine and analyze the effect of implementing the free expression learning method on the drawing skills of fourth-grade students at SD Negeri 102 Palembang. The background of this research is the low level of students’ drawing skills, which tend to be rigid, as well as their lack of confidence in expressing creative ideas due to the dominance of conventional teaching methods. The research method used is the experimental method. The results of data analysis show that there is a significant effect of the free expression learning method on students’ drawing skills. This is evidenced by the higher average post-test score of the experimental class compared to the control class, and the hypothesis test results show a significance value (Sig. 2-tailed) of 0.001, which is smaller than 0.05. Therefore, it can be concluded that the free expression learning method is effective in improving the drawing skills of fourth-grade students at SD Negeri 102 Palembang